Humanistic Literacy in Gender-Based Learning in the Digital Era - Fia Alifah Putri; Yuda Wira Setiawan; Sasmitro Anggoro; M. Wais Alqarni; Nurbaiti Agustina Ritonga (Yayasan Zia Salsabila, 2023)
The research aims to analyze digital-based humanist literacy in the learning process. This research uses the literature study method. The results of this research show that digital-based humanist literacy can make it easier for students to learn and be curious about the aspect of gender equality. This digital-based humanist literacy is usually used during distance education. The challenge faced is that when learning takes place, educators are already humanistic, but students are not yet humanistic. On the other hand, when distance learning uses digital, not only educators are humanistic, but students are also required to be humanistic. Digital learning can be carried out face to face.